2011
DOI: 10.6009/jjrt.67.221
|View full text |Cite
|
Sign up to set email alerts
|

Basic Evaluation of Sampling Step Angle and Spatial Resolution in Continuous Rotating Acquisition with SPECT

Abstract: In the data sampling in single photon emission computed tomography (SPECT), the continuous rotating acquisition method has high clinical utility. There have been various reports about the optimum sampling step angle for continuous rotating acquisition. Objective evaluation was performed visually and by measuring spatial resolution with a column phantom to find the optimum sampling step angle for continuous rotating acquisition. In locations far from the rotation center, a large sampling step angle produced art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Cao et al (15) reported that the image quality of CRRA was similar to that of the SS mode. In addition, Kangai et al (16) showed that the FWHM obtained with an optimal sampling step angle did not differ between CRRA and the SS mode. Our results agree with those of the previous studies and indicate that CRRA is appropriate for 123 I-FP-CIT SPECT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al (15) reported that the image quality of CRRA was similar to that of the SS mode. In addition, Kangai et al (16) showed that the FWHM obtained with an optimal sampling step angle did not differ between CRRA and the SS mode. Our results agree with those of the previous studies and indicate that CRRA is appropriate for 123 I-FP-CIT SPECT imaging.…”
Section: Discussionmentioning
confidence: 99%